(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
In the article presented materials By study the role and importance of management accounting in enterprise management. In the article by the author considered issues of the need for management accounting as an innovative type of economic accounting. The author noted that the use of management accounting at an enterprise is a consequence solution to the problem of making effective and rational current and long-term management decisions at a given enterprise.